The surface chemistry of tin(IV) oxide: Defects, doping and conductivity. - Egdell, R (1994)
A review is given of the application of contemporary UHV surface science techniques to the study of the surface chemistry of tin(IV) oxide, SnO 2. Topics of particular interest include the nature of electronic states associated with oxygen vacancies at SnO 2 surfaces; changes in electronic structure that may be brought about by doping (especially with Sb); and the relationship between bulk doping levels and surface dopant concentration. Interest focusses ultimately on our recent attempts to produce n-type doping of SnO 2 thin films in the near surface region by implantation of ions including Sb, Bi and Nb and on the conductivity of single crystal surfaces. © 1995 Elsevier B.V. All rights reserved.